PENGARUH KURIKULUM MERDEKA, EFIKASI DIRI DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI SEKOLAH MENENGAH ATAS LEBAK BANTEN - M. Muslim; Muhammad Arifin; Samudi (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
Performance is a core aspect for the birth of the goals and functions of education or learning in schools. Meanwhile, teacher performance is strongly influenced by several components or factors, including: independent curriculum, self-efficacy and professional competence and job satisfaction. This research aims to examine and analyze the influence of the independent curriculum, job satisfaction and professional competence with self-efficacy as an intervening variable. The research sample consisted of 100 respondents. This research approach uses quantitative survey research, and data collection techniques use observation, questionnaires, documentation and literature. The results of this research show that: Hypothesis 1 is accepted, the independent curriculum has an effect on job satisfaction. Hypothesis 2 is accepted, self-efficacy influences job satisfaction. Hypothesis 3 is accepted, professional competence influences job satisfaction. Hypothesis 4 is accepted, the independent curriculum influences teacher performance. Hypothesis 5 is accepted, self-efficacy influences teacher performance, Hypothesis 6 is accepted, professional competence influences teacher performance. Hypothesis 7 is accepted, job satisfaction influences teacher performance. Hypothesis 8 is accepted, the independent curriculum indirectly influences teacher performance. Hypothesis 9 is accepted, self-efficacy indirectly influences teacher performance. Hypothesis 10 is accepted, professional competence indirectly influences teacher performance.